Esteban montejo, the story of Cuba’s last cimarrón slave - United Nations Educational, Scientific; Cultural Organization; Guillermo G. Espinosa (The UNESCO Courier, 2024)
In the early 1960s, Cuban writer and ethnologist Miguel Barnet collected the testimony of 104-year-old Afro-descendant Esteban Montejo. The hugely influential account he drew up is a unique document on the condition of captives and the violence of the slavery system.